Perancangan Sistem Deteksi Tingkat Kemiringan Jalan Sederhana Dengan Metode Otsu Thresholding Menggunakan Colab - Bagus Nurhannudin (Router : Jurnal Teknik Informatika dan Terapan, 2024)
This research focuses on the development of a simple system for detecting road slopes using the Otsu Thresholding method. The primary objective is to create an effective and efficient system capable of identifying different road slope levels accurately. The system utilizes image processing techniques, where the Otsu Thresholding method is applied to differentiate between road surfaces and surrounding environments. By analyzing these images, the system determines the degree of road slope. This study emphasizes the importance of accurate road slope detection for improving road safety and maintenance. The observation method was employed in this research to gather relevant data and evaluate the system's performance. The results demonstrate that the designed system is capable of effectively detecting various road slope levels, providing a valuable tool for transportation infrastructure monitoring.